The impact of perfumes and cosmetic products on human health: a narrative review - Alblooshi, Sharifa (Frontiers in Toxicology, 2025)
BackgroundThe use of perfumes and cosmetic products is widespread, serving personal hygiene, aesthetic, and olfactory functions. However, concerns have been raised regarding the potential health impacts associated with long-term exposure to various ingredients used in these products.ObjectivesThis narrative review aims to synthesize evidence on the health risks associated with perfumes and cosmetics, focusing on specific health concerns, including fertility, respiratory health, cancer risk, allergies, skin disorders, endocrine disruption, and neurological effects. It also discusses the presence of heavy metals in cosmetics, regulatory challenges, and the need for transparency in ingredient disclosure.MethodsA comprehensive review of literature published between 2005 and 2025 was conducted, examining findings from interdisciplinary studies relevant to the health impacts of cosmetic and fragrance products. The review highlights health concerns linked to specific chemical components, including synthetic chemicals such as phthalates, parabens, and volatile organic compounds (VOCs).ResultsThe findings indicate that many synthetic chemicals in perfumes and cosmetics are associated with adverse health outcomes. These include allergies, respiratory issues, endocrine disruption, reproductive problems, and potentially cancer. Heavy metals in cosmetics also pose significant health risks. Despite regulatory guidelines, the cumulative and long-term effects of combined exposure to multiple cosmetic ingredients remain poorly understood and inadequately addressed.ConclusionThere is a pressing need for stricter regulatory oversight and improved transparency in ingredient disclosure to safeguard consumer health. Further research is required to clarify the long-term health risks associated with the daily use of cosmetic products and to develop safer alternatives.